The right of people with special needs to work and protection from psychological and social risks in Algeria ligislation - Bouchrea, Fatima (Journal of Human Sciences, 2023)
Work is a constitutional right enshrined in all state constitutions, recognized and guaranteed by the Universal Declaration of Human Rights of 1948, and it was affirmed for all members of society, including people with special needs, taking into account all the difficulties and obstacles that this special group may face in the field of work, as well. In addition to the various and various risks that they may face as groups of people with special needs, which require taking care and dealing with them in particular within the field of work.